2017
DOI: 10.1186/s12859-017-1608-x
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of the fitness sharing technique in an evolutionary algorithm to analyze the fitness landscape of the genetic code adaptability

Abstract: BackgroundThe canonical code, although prevailing in complex genomes, is not universal. It was shown the canonical genetic code superior robustness compared to random codes, but it is not clearly determined how it evolved towards its current form.The error minimization theory considers the minimization of point mutation adverse effect as the main selection factor in the evolution of the code. We have used simulated evolution in a computer to search for optimized codes, which helps to obtain information about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
4
7
0
Order By: Relevance
“…In terms of minimization of amino acid replacements resulting from point mutations in codons, measured here by the average conductance, the SGC is placed between the M 1 codes, characterized by the lowest conductance, and the codes from the M 2 and M 3 models. In agreement with our simulation study, other analyses also showed that the SGC is not perfectly optimized in this respect and better codes can be found [11,44,50,57,58,[87][88][89]. Therefore, it is possible that the assignments of amino acids to codons occurred in accordance with other mechanisms, while the minimization of mutation errors was adjusted by the direct optimization of the mutational pressure around the established genetic code [90][91][92][93][94].…”
Section: Discussionsupporting
confidence: 88%
“…In terms of minimization of amino acid replacements resulting from point mutations in codons, measured here by the average conductance, the SGC is placed between the M 1 codes, characterized by the lowest conductance, and the codes from the M 2 and M 3 models. In agreement with our simulation study, other analyses also showed that the SGC is not perfectly optimized in this respect and better codes can be found [11,44,50,57,58,[87][88][89]. Therefore, it is possible that the assignments of amino acids to codons occurred in accordance with other mechanisms, while the minimization of mutation errors was adjusted by the direct optimization of the mutational pressure around the established genetic code [90][91][92][93][94].…”
Section: Discussionsupporting
confidence: 88%
“…The random codes represent only a very tiny fraction of all possibilities and are not necessarily representative of the whole space of the theoretical codes. The EA technique was already successfully applied in various studies on the optimality of the genetic code [ 23 , 24 , 59 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…This assumption follows the adaptation hypothesis, which claims that the SGC evolved to minimize harmful consequences of mutations or mistranslations of coded proteins [Woese, 1965, Sonneborn, 1965, Epstein, 1966, Goldberg and Wittes, 1966, Haig and Hurst, 1991, Freeland and Hurst, 1998, Freeland et al, 2000, Gilis et al, 2001. Although this code did not turn out perfectly optimized in this respect [B lażej et al, 2018a, B lażej et al, 2016, Massey, 2008, Novozhilov et al, 2007, Santos et al, 2011, Santos and Monteagudo, 2017, B lażej et al, 2018b, B lażej et al, 2019b, Wnetrzak et al, 2019, it shows a general tendency to error minimization in the global scale. This property is better exhibited by its alternative versions [B lażej et al, 2018c, B lażej et al, 2019a], which occurred later in the evolution.…”
Section: Resultsmentioning
confidence: 83%